Lietuvos demografinė kaita: ką atskleidžia gyventojų surašymai : mokslo studija Demographic development of Lithuania: what do the population censuses reveal - Žibas, Karolis (Vytautas Magnus University, 2016)
Demographic situation of Lithuania has deteriorated for more than two decades and continues to be very difficult. Data of the vital statistics and of various sample surveys are commonly used for an assessment of the demographic situation. Meanwhile, a very rich data of population census of the entire population are employed only rarely. Therefore, this study has several aims. The main aim of the study is to obtain the new knowledge on demographic development of Lithuania using census data and to reveal the impact of long-term historical changes of socio-demographic structures of population and demographic processes on current demographic situation as well as their possible continuity in the future. Other important aim of this study is to draw attention of researchers and public policy-makers to the rich population census data which allow to understand the demographic situation not only on the total population level but also on various socio-demographic segments and in the long-term context of the demographic development. The information basis of this study includes: first, the micro-data of the Lithuanian 2011 population and housing census which have been a major source of the research; second, for the comparative analysis, the micro-data of Lithuanian 2001 population and housing census have been used; third, available and comparable aggregate data of previous censuses (1989, 1979, 1970, 1959, 1923, and 1897), which permit to disclose demographic trends in the long historical perspective, have been analyzed. The study consists of three parts: the first part - "Socio-demographic composition of Lithuanian population" (by the age, education, ethnicity, foreign born population); the second part - "The changes in the demographic processes" (marital behaviour and fertility); and the third part - "The empirical sources and methodology of the study." [...]